"South-to-South" Dialogues: Comparative Literature as a Decolonizing Power (Global Journal of Human-Social Science, 2021)
The article proposes that south-to-south dialogues could act as deconstructive acts that undermine the centrality power disposed on post-colonial relations. Discussing the implications of decolonial theories to the understanding and the articulation of these deconstructions, the article investigates both the notion of invention of the other and of the same as proposed by Jacques Derrida. Basing the analyses of the colonial structure in the invention of the truth through language, the article proposes the reading of other inventions, other rationalities and other relations, through an approximate analysis of Barren lives (Vidas Secas), by the Brazilian writer Graciliano Ramos, and Sleepwalking land (Terra Sonâmbula), by Mozambican literate Mia Couto. In both books, what interest us is the invention of the hinterland -sertão and savana -and how they portrait identities that relate to otherness, configuring a south-to-south decolonial dialogue.
Keywords: literature; decolonial theory; hinterland; brazil; Mozambique